Third time lucky? Reconciling EU climate and external energy policy during energy security crises. Issue 3 (3rd April 2023) - Giuli, Marco; Oberthür, Sebastian
ABSTRACT: The Russian aggression against Ukraine brought energy security to the top of the European policy agenda. Existing literature suggests that the prioritization of energy security would come at the expense of climate policy. We argue that the EU's response to the Russian invasion of Ukraine may constitute a departure from this pattern. Our assessment shows a higher level of coherence of objectives and instruments between energy security and climate objectives than the EU's energy policy responses to previous crises with Russia, notably the gas supply crisis of 2009 and the annexation of Crimea in 2014. While some uncertainty about final outcomes remains, we argue that change in several contextual conditions helps explain coherent policy outputs and make coherent outcomes more likely on the occasion of the present crisis.